The physiological significance of changes in β-glucuronidase activity - Kerr, Lynda M. H. (The University of Edinburgh, 1949)
1. Phenol-glucuronide is a convenient substrate for the assay of (ß-glucuronidase,using the Folin and Giocalteu (1927) reagent for the estimation of free phenol.

2. ß-Glucuronidase from mouse liver, kidney and spleen contains two fractions which may be separated by ammonium sulphate precipitation. Uterus contains only one fraction. For total enzyme and fraction B in liver,kidney and spleen a citrate buffer at pH 5.2 was used in the estimation and for uterine enzyme and fraction A in liver,kidney and spleen a buffer at pH 4.5. A substrate concentration of 0.015M was used in all cases.

3. The mean recovery of added phenol in the assay procedure was 100; ,and the standard deviat.ión of a single observation from the mean was 0.6%

4. The effect of menthol in increasing the glucuranidase activity in liver and kidney is secondary to I repair following damage provoked by that agent rather than due to its glucuronidogenic properties. This is confirmed by the changes in enzyme activity observed after administration of many nonglucuronidogenic compounds and by the manner in which the enzyme activity reflected the sex -linked nature of chloroform poisoning in kidney.

5. The two enzyme fractions in liver and kidney respond indifferently to agents causing changes in the enzyme activity.

6. In uterus,as in other organs,changes in glucuronidase activity reflect changes in growth. The action of oestrone on the enzyme is antagonised by testosterone and progesterone.

7. Oestrone causes a marked increase in glucuronid&:: ase activity in liver accompanied by an increase in cell division. Both effects may be antagonised by testosterone and progesterone. Oesftadiol,oestriol and oestriol- glucuronide,in doses comparable to that of oestrone, are without effect on liver enzyme and their action in stimulating mitosis is slight.

8. During liver regeneration,as after partial hepatectomy,uterine weight and glucuronidase activity increaee_in ovariectomised mice in the absence of administered oestrogen. Testosterone and progesterone antagonise this effect.

9. Colchicin.e,substituted stilbenes and anilines and the antiolic acid factor,known to inhibit cell proliferation,are without effect on the in vitro hydrolysis of phenol -glucuronide by glucuronidase. Saccharate,an efficient inhibitor of glucuronidase in vitro,is without effect on mitosis.

10. Sorbic acid is a most efficient inhibitor of cell proliferation.

11. A depression in the high glucuronidase level in an organ in which mitosis had been stimulated is only obtained after an inhibition of cell division.